Analisis Prestasi Belajar IPA Berdasarkan Status Sosial Ekonomi Orang Tua dan Minat Belajar IPA Peserta Didik - Nunung Setiati; Jumadi Jumadi (Postgraduate, University of Mataram, 2022)
This study aims to analyze science learning achievement based on socio-economic status and students' interest in learning science. This research is a qualitative research. The qualitative research used is descriptive qualitative research. The data were obtained from the scores given by the previous science teacher. Furthermore, data were collected by using in-depth interviews and participatory observation to data sources. The collected data was then validated by triangulation technique. Triangulation carried out in this study includes triangulation of techniques and triangulation of sources. The collected data is then analyzed using the Miles and Huberman model. In this technique, there are four stages of analysis, namely the stage of data collection, data reduction, data display, and conclusion. Based on the results of the study, it was found that the economy of parents has a very important role in the achievement of students in science learning. This happens because students need smartphones as a facility in daring to learn from home and parents must provide them. In addition, learning interest during the covid-19 pandemic is also very important to foster a sense of learning so that students' learning achievement can increase